Serum levels of anti-CCP antibodies, anti-MCV antibodies and RF IgA in the follow-up of patients with rheumatoid arthritis treated with rituximab - Fabris, Martina (Auto Immun Highlights, 2010)
Rheumatoid arthritis (RA) is characterized by the presence of circulating rheumatoid factor (RF) and anticitrullinated peptide antibodies (ACPA), which are positive in about 70–80% of patients. APCA have a higher specificity and therefore a higher diagnostic power than RF, but are less informative than RF in monitoring the course of the disease in patients under treatment. Recently, it has been reported that the anticitrullinated vimentin (a-MCV) antibody test can identify a particular subgroup of APCA that may be negative for anticyclic citrullinated peptide (a-CCP) antibodies. Concerning RF, the RF IgA isotype has been described as a more specific marker of erosive joint damage than total RF. The aim of our study was to monitor the levels of a-CCP, a-MCV, total RF and RF IgA in the follow-up of patients with RA treated with B-lymphocytedepletive rituximab (RTX), to detect any differences or peculiarities in patterns of these autoantibodies, especially in relation to their potential use as predictive markers of therapeutic response. We studied 30 patients with RA treated with RTX. All patients were previously unresponsive to at least 6 months of therapy with disease-modifying antirheumatic drugs (DMARDs; methotrexate, leflunomide, cyclosporine, chloroquine) and/or at least 6 months of therapy with anti-TNF biologics. The evaluation of response to RTX was made at month +6 using the EULAR criteria (DAS28). a-CCP, a-MCV, total RF and RF IgA were determined at baseline (before the first infusion of RTX) and after 1, 3 and 6 months. In serum samples obtained before treatment two cytokines essential for Blymphocyte proliferation, interleukin 6 (IL-6) and B-lymphocyte stimulator (BLyS) were also determined. In all patients a significant and consistent reduction in all the tested antibodies was found during follow-up, with no differences in respect of the degree of response to RTX. Of note, at baseline, generally a higher titre of all autoantibodies was seen in patients who then showed a better response to RTX. Finally, there were no differences in serum concentrations of IL-6 and BLyS in patients in relation to the presence or absence of the autoantibodies investigated, nor was there any significant correlation between the serum concentrations of the cytokines and the titres of the autoantibodies. Thus, neither a-MCV compared to a- CCP, nor RF IgA compared to routine total RF, provided any additional predictive information in the follow-up of patients with RA treated with RTX.